Iran's Pharmaceutical Sectoral Innovation System - Bahman Kargar Shahamat; Mohamad Reza Taghva; Seyyed Habibollah Tabatabaiean (Islamic Azad University, 2017)
Abstract By reviewing economic performance, two main phenomena could be identified: The first phenomenon is prior to the third wave of the Industrial Revolution in which limited resources are the predominant input; in other words, physical and natural resources are much more credited than human resources. The second phenomenon resonates with the third wave of industrial revolution to the present time, suggesting the pivotal role of humans in production and accumulation of wealth, in which limited resources are no longer considered as predominant input. The present research seeks to understand the behavioral logic of the players of Iran's pharmaceutical sector so as to infer the innovative treatment of the firms in this sector. The concept of innovative system is indebted to the efforts economists and other scientists have made by analyzing economic development based upon technological development. Meanwhile, sectoral innovation system (SIS) is a tool for analyzing a technological sector in the context of evolutionary economics with an emphasis on institutional capabilities. The structure of such an approach is composed of some components through which performance analysis of certain technological sector could be made possible. In research, we use expert panel with 12 experts from Universities, Companies, Governmental institutes. The current study wishes to explain structural model of institutional elements in this technological sector. Subsequently, in light of such an explanation, structural elements of this sector would be analyzed through identification of legal and regulatory framework, innovative culture, innovative infrastructure, financial resources, information resources, technology transfer mechanisms, commercialization support and marketing.